2015
DOI: 10.4137/ebo.s21832
|View full text |Cite
|
Sign up to set email alerts
|

Apparent microRNA-Target-specific Histone Modification in Mammalian Spermatogenesis

Abstract: BACKGROUNDEpigenetics is an important mRNA expression regulator. However, how distinct epigenetic factors, such as microRNAs (miRNAs) and promoter methylation, cooperatively regulate mRNA expression is rarely discussed. Recently, apparent miRNA regulation of promoter methylation was identified by bioinformatic analysis; however, it has not yet been experimentally confirmed. If miRNA regulation of other epigenetic factors were identified, it would reveal another layer of epigenetic regulation. In this paper, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Consistent with our findings, six of our eleven (55%) miRNAs identified in the TBI cohort (let-7a-5p, miR-16-2-5p, -93-5p, -122-5p, -223-3p and -375-3p) were identified in an independent study focused on identifying miRNA with a role in histone modification, including H2A. Only two of our eleven (18%) miRNAs from the WTLI cohort (miR-181a-5p and -200c-3p) were present (47). In addition to DNA damage repair, K48 ubiquitination (GO:0070936) regulates p53 homeostasis (48,49).…”
Section: Discussionmentioning
confidence: 79%
“…Consistent with our findings, six of our eleven (55%) miRNAs identified in the TBI cohort (let-7a-5p, miR-16-2-5p, -93-5p, -122-5p, -223-3p and -375-3p) were identified in an independent study focused on identifying miRNA with a role in histone modification, including H2A. Only two of our eleven (18%) miRNAs from the WTLI cohort (miR-181a-5p and -200c-3p) were present (47). In addition to DNA damage repair, K48 ubiquitination (GO:0070936) regulates p53 homeostasis (48,49).…”
Section: Discussionmentioning
confidence: 79%
“…Gene expression is influenced by changes in chromatin states through epigenetic mechanisms involving post‐translational modifications of histones (Lindeman et al., ; Ruthenburg, Li, Patel, & Allis, ). While post‐translational modifications of H3K27ac are involved in transcriptional activation (Cao et al., ; Czermin et al., ; Kuzmichev, Nishioka, Erdjument‐Bromage, Tempst, & Reinberg, ; Müller et al., ; Santos & Dean, ; Taguchi, ), those of H3K27me3 result in transcriptional silencing (Lee, ; Santos & Dean, ; Tsai et al., ; Zhao, Sun, Erwin, Song, & Lee, ). Our study is the first to demonstrate the levels of post‐translational changes of H3K27ac vs H3K27me3 in bull spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…These above suggested that miRNAs down-regulated in tumor possibly may target epigenetically important genes up-regulated in tumor. Since interaction between epigenetics and miRNAs were recently proposed [44], [45], this observation sounds feasible.…”
Section: Suz12mentioning
confidence: 96%